2010
DOI: 10.1111/j.1365-2966.2010.17487.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength study of Chandra X-ray sources in the Antennae

Abstract: We use Wide-field InfraRed Camera (WIRC) infrared (IR) images of the Antennae (NGC 4038/ 4039) together with the extensive catalogue of 120 X-ray point sources to search for counterpart candidates. Using our proven frame-tie technique, we find 38 X-ray sources with IR counterparts, almost doubling the number of IR counterparts to X-ray sources that we first identified. In our photometric analysis, we consider the 35 IR counterparts that are confirmed star clusters. We show that the clusters with X-ray sources … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…Sources X45 and X49 are in our list but not in Clark et al (2011). They are coincident with clusters that have ages of ≈50 Myr and are somewhat fainter than most of the very young clusters in our sample, and hence may not have been detected in the WIRC observations used by Clark et al (2011).…”
Section: Optical Star Cluster Counterparts To Xrbsmentioning
confidence: 98%
See 4 more Smart Citations
“…Sources X45 and X49 are in our list but not in Clark et al (2011). They are coincident with clusters that have ages of ≈50 Myr and are somewhat fainter than most of the very young clusters in our sample, and hence may not have been detected in the WIRC observations used by Clark et al (2011).…”
Section: Optical Star Cluster Counterparts To Xrbsmentioning
confidence: 98%
“…In the remaining cases, no obvious optical counterpart to the candidate XRBs is observed. Clark et al (2011) found IR counterparts (within 2 ) to 32 of the X-ray sources listed in the Zezas et al (2006) catalog that are within the main body of the Antennae (see their Figure 1). Excluding sources that are beyond the field of view of the ACS images used here, close to the northern nucleus, and those that may be detections of diffuse plasma, we have 17 sources in common with Clark et al (2011).…”
Section: Optical Star Cluster Counterparts To Xrbsmentioning
confidence: 99%
See 3 more Smart Citations